KURIKULUM DAN PENDIDIKAN BERBASIS PROYEK MENDORONG KREATIVITAS DAN KOLABORASI - Nurmaliati; Unan Yusmaniar Oktiawati; Al Ikhlas; Heri Kurnia; Ade Taufan; Dhiraj Kelly Sawlani (EDU RESEARCH, 2024)
Project-based learning (PBL) is an innovative approach to curriculum development aimed at fostering creativity and collaboration among students. This approach integrates student-centered learning with real-world projects relevant to professional environments and everyday life. In project-based learning, students actively engage in exploration, investigation, and the creation of products or solutions, motivating them to think critically, work in teams, and develop communication skills. This article explores how project-based curricula are designed and implemented to promote deep student engagement, enhance 21st-century skills, and create meaningful learning experiences. Additionally, the challenges and strategies for implementing project-based education are discussed, including the critical role of teachers as facilitators and the integration of technology to support learning. Consequently, this approach emerges as a viable solution for creating a more relevant and adaptive education system in the era of globalization.